P113 Online case-based education substantially improved rheumatologists' confidence and competence in managing SLE and selecting appropriate treatments. (23rd March 2020) - Bell, Elaine; McCarthy, Robert; Vollenhoven, Ronald van
Abstract : Background/Purpose: The prognosis for patients with systemic lupus erythematosus (SLE) has improved in recent years, but many patients fail to achieve optimal disease control. We assessed whether an online case-based CME activity could improve rheumatologists' confidence in managing SLE and in selecting appropriate treatments for their patients. Methods: Rheumatologists participated in a segmented online multi-media activity consisting of videos portraying realistic physician–patient interaction followed by a test question and expert commentary. Educational effect was assessed using a repeated-pair design, pre-/post-assessment. A Chi-square test of independence determined if a statistically significant improvement (5% significance level, P <0.05) existed in the number of correct responses between the pretest and posttest scores. Cramer's V estimated the effect size of the education. The activity launched 26 March 2019 with data collection through 29 April 2019. Results: 35% of rheumatologists' (n=46) answered all 3 questions correctly at baseline rising to 85% post assessment (P <.001) Significant improvement in knowledge of the proportion of SLE patients testing positive for anti–nuclear antibodies (72% at baseline, 93% post assessment; P <.01), and significant improvement in treatment choice for a patient who experienced worsening symptoms following initial success with prednisone, hydroxychloroquine and methotrexate (59% at baseline, 91% post asessment; P <.001) Extensive educational impact (Cramer's V =0.277) on knowledge and competence overall with 30% of rheumatologists reporting greater confidence in their ability to treat SLE symptoms 38% of participants reported an intent to make changes in their practice based on what they learned; of those who intended to make a change, 92% were highly committed to implementing these changes Conclusions: Participation in this segmented online multi-media activity was highly effective in improving rheumatologists' confidence and competence in treatment selection and management of SLE. The extensive impact of this education should translate into improvements in clinical practice. Acknowledgement: Supported by GlaxoSmithKline